ANALISIS POSTUR KERJA KARYAWAN BAGIAN PENGELASAN TIANG LAMPU JALAN DENGAN MENGGUNAKAN METODE QEC DAN RULA UNTUK MENINGKATKAN ERGONOMI DI PT.OPQ - Kurnia, Tyas Eka; Chirswahyudi, Chirswahyudi; Harjuanto, Klangga Aziz (Politeknik META Industri Cikarang, 2025)
The analysis was carried out in the process of welding street light poles at PT. OPQ, several operators in this section complained of pain in their body parts. Evaluation is carried out by measuring pain complaints using the Standard Nordic Questionnaire to determine whether there are physical complaints in employees. After that, the QEC and RULA methods were used to assess work posture risks. The analysis was carried out directly on assembling workers using 5 samples of body postures and the one with the highest risk level was the posture when carrying out the welding process, with a final score of 7 (seven) high risk levels, requiring action now. The cause of the high risk level is because they are still using manual systems and body postures that are not yet ergonomic. There is a need for adequate tools, namely: pulleys and work tables to improve company ergonomics and productivity